Reconciling Islamic Jurisprudence and Hadith in al-Andalus in the 5th/ 11th Century: Ibn al-Ṭallā‘ (d. 497/1104) and His Aqḍiyat Rasūl Allāh - Akmaluddin, Muhammad (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The study of Muwaṭṭa’ Mālik and the Mālikī school dominated in al-Andalus from the 2nd/8th century to the 3rd /9th century. The following two centuries marked the decline of Muwaṭṭa’ Mālik studies in al-Andalus. Therefore, the study of the 5th/11th is very important to illustrate how the transition from the domination of Muwaṭṭa’ Mālik to the domination of other books, in this case is al- Andalus. One of them is the work of Muḥammad bin Farj al-Qurṭubī al-Mālikī (d. 497/1104), known as Ibn al-Ṭallā‘ in his book, Aqḍiyat Rasūl Allāh ṣallā Allāh ‘alaihi wa sallam. This research employs a qualitative approach, literature studies and content analysis. This article discusses the criticism of Ibn al- Ṭallā’ on the orthodoxy of the Mālikī school and the process of reconciling hadith and Islamic jurisprudence (fiqh) in al-Andalus in the 5th/11th century. Ibn al-Ṭallā‘enjoyed academic freedom amidst political and identity chaos at that time. With such chaos, views of non-Mālikī Islamic scholars were more numerous and they were getting freedom of expression. Hence, he was welcome to depart from Mālikī orthodoxy by quoting opinions from other schools and comparing them. The combination of fiqh and hadith sources, as well as the combination of the opinions of Mālik ibn Anas and other schools, became an achievement for Ibn al-Ṭallā‘. This achievement went through several processes and stages, especially since the Mālikī school and Muwaṭṭa’ still dominated since they became the official schools of the Umayyad dynasty in al-Andalus in the 2nd/8th century until the 3rd/9th century.